COINDAG: A database integration with application engine to improve accessibility to information during infodemic and pandemic Covid-19 in Enhancing Data-Driven Decision-Making / Mohammad Azuwadi Mohd Yasin, Yarina Ahmad and Marni Ghazali - Mohd Yasin, Mohammad Azuwadi; Ahmad, Yarina; Ghazali, Marni (2021)
Infodemic can be defined as too much information, including false or misleading information in the digital and physical environment during a disease outbreak (World Health Organization, 2020). Almost every minute, people receive too much information related to COVID-19, yet people are not sure of the truth and accuracy of the news or information. Hence, the false news that is becoming more prevalent nowadays must be addressed immediately (Sualman, 2020). Furthermore, Tedros Adhanom Ghebreyesus, Director-General of the World Health Organization (WHO) mentioned, that in their efforts to fight the COVID-19 infodemic, WHO have partnered with the United Kingdom government to run Stop the Spread, an awareness campaign on the risks of incorrect and false information about the pandemic. In addition, Antonio Guterres, Secretary-General of the United Nations (UN) mentioned, other than COVID-19 as a common enemy; the "infodemic" of misinformation is another challenge; to overcome the coronavirus; hence, urged to promote facts and science urgently.